New energy automobile with sound absorption, noise reduction and light weight

By using a combined structure of fabric layer, polyurethane foam layer, glass wool layer and non-woven layer in the front hatch of new energy vehicles, the problems of large weight, poor sound absorption and low aesthetics are solved, and lightweight and sound absorption reduction are achieved The improvement of noise and aesthetics extends the vehicle's range and reduces noise.

CN119190202APending Publication Date: 2024-12-27ZHANGJIAGANG CHANGTAI AUTO TRIM MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310757819.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-26
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The front hatch of new energy vehicles is usually made of heavy plastic parts, with poor sound absorption and noise reduction performance and unsightly, which affects the range and driving experience.

Method used

Using a front hatch structure composed of fabric layer, polyurethane foam layer, glass wool layer and non-woven fabric layer, the porous structure of polyurethane foam and the micro-porous structure of glass wool can be enhanced by HDPE. The adhesive film and spunbond non-woven fabric enhance overall strength and aesthetics.

Benefits of technology

The front hatch cover is lightweight, sound absorption and noise reduction and aesthetics improved, the vehicle has a longer range, and the noise is significantly reduced in the medium and high frequency bands. The weight is lower than that of the traditional plastic front hatch cover, and the fabric color can be customized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119190202A_ABST
    Figure CN119190202A_ABST
Patent Text Reader

Abstract

The invention relates to a sound-absorbing, noise-reducing and light-weight new energy automobile, and mainly solves the problems that a front cabin cover of a new energy automobile in the prior art is generally made of a plastic part, and is heavy, poor in sound-absorbing and noise-reducing performance and not attractive in appearance. The sound-absorbing, noise-reducing and lightweight new energy automobile comprises an automobile body and an automobile head, the automobile head comprises an engine hood, a front cabin cover and a cavity for containing cables, and the front cabin cover sequentially comprises a fabric layer, a first bonding layer, a polyurethane foam layer, a second bonding layer, a glass wool layer, a third bonding layer and a non-woven fabric layer from top to bottom; the preparation method of the front cabin cover comprises the following steps: a, sequentially stacking the material layers from top to bottom: the fabric layer, the first bonding layer, the polyurethane foam layer, the second bonding layer, the glass wool layer, the third bonding layer and the non-woven fabric layer; and b, the seven layers of materials in the step a are heated at the same time and then subjected to compression molding to obtain the front hatch cover, the problem is well solved, and the method can be used for industrial production of new energy automobiles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy vehicles, and in particular to a new energy vehicle with sound absorption, noise reduction and light weight. Background Art

[0002] With the development of the automobile industry, new energy vehicles have entered a period of rapid development. New energy vehicles use batteries instead of traditional generators as power. The batteries are laid at the bottom of the car body, forming a cavity under the front hood to accommodate cables. The OEMs often set up a front hatch cover to cover the cables, and even configure a storage box to improve the space utilization of the front cavity. However, the conventional front hatch is made of plastic injection molding, and the gram weight is usually 2500~3000g / m 2 The heavy weight and heavy vehicle load will aggravate the problem of shortened battery life. In addition, the single color and poor aesthetics of plastic parts make it increasingly unable to meet the increasingly stringent aesthetic requirements of consumers. On the other hand, the sound absorption performance of plastic front hoods is relatively poor, and the current noise of the motor and the noise during driving seriously affect the driving experience of the drivers and passengers. Therefore, it is particularly important for new energy vehicles to develop a lightweight, sound-absorbing and noise-reducing front hood that is more beautiful.

[0003] HDPE is the abbreviation of high-density polyethylene (High Density Polyethylene), also known as low-pressure polyethylene. It is a thermoplastic resin with high crystallinity, non-polarity, and a certain degree of translucency. It has good heat resistance and cold resistance, good chemical stability, high rigidity and toughness, and good mechanical strength. Its dielectric properties and resistance to environmental stress cracking are also good. Its hardness, tensile strength, and creep properties are better than those of low-density polyethylene.

[0004] Chinese patent CN205273637U discloses a composite passenger car hood, which consists of an outer panel and an inner panel, wherein the outer panel is molded by continuous glass fiber fabric prepreg, and the inner panel is injection molded by LFT process, and the inner panel and the outer panel are assembled by gluing; wherein the material matrix used for the outer panel is epoxy resin or modified epoxy resin or bismaleimide resin, and the material matrix used for the inner panel is nylon; the weight of the hood product is greatly reduced, and it can be used to replace the existing metal hood and reduce the energy consumption of the car; however, its sound absorption and noise reduction effect is poor, and its aesthetics is insufficient.

[0005] Chinese patent CN 209505138 U discloses a front hood sound insulation and heat insulation pad, including a pad body, the shape of the pad body is adapted to the front hood and is clamped on the front hood, the pad body includes a first heat-resistant layer, a first moisture-proof layer, a first sound insulation and heat insulation layer, a shaping layer, a second sound insulation and heat insulation layer, a second moisture-proof layer and a second heat-resistant layer which are stacked and bonded in sequence; wherein the first and second heat-resistant layers are PET layers, the first and second moisture-proof layers are PE film layers, the first and second sound insulation and heat insulation layers are PUR layers, and the shaping layer is a phenolic resin glass fiber cloth layer; it has a certain sound absorption and heat insulation effect, but its sound absorption and noise reduction performance needs to be further improved, and the overall front hood is heavy and not aesthetically pleasing. Summary of the invention

[0006] The technical problem to be solved by the present invention is that in the prior art, the front hood of a new energy vehicle is usually a plastic part, which has the problems of heavy weight, poor sound absorption and noise reduction performance and unsightly appearance. A sound-absorbing and noise-reducing, lightweight new energy vehicle is provided, which has the advantages of lightweight, good sound absorption and noise reduction performance and beautiful front hood appearance.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: a sound-absorbing, noise-reducing, lightweight new energy vehicle, comprising a body 12 and a front 11, the front 11 comprising an engine hood 8, a front hatch 9 and a cavity 10 for accommodating cables, wherein the front hatch 9 comprises, from top to bottom, a fabric layer 1, a first bonding layer 2, a polyurethane foam layer 3, a second bonding layer 4, a glass wool layer 5, a third bonding layer 6 and a non-woven fabric layer 7; and a preparation method of the front hatch 9 comprises the following steps: a. stacking the material layers from top to bottom in sequence: a fabric layer 1, a first bonding layer 2, a polyurethane foam layer 3, a second bonding layer 4, a glass wool layer 5, a third bonding layer 6 and a non-woven fabric layer 7; b. heating the seven layers of material in step a at the same time, and then compression molding them to obtain a front hatch.

[0008] In the above technical solution, preferably, the density of the polyurethane foam layer 3 is 10-18 kg / m 3 , thickness is 15~25mm.

[0009] In the above technical solution, preferably, the first adhesive layer 2, the second adhesive layer 4 and the third adhesive layer 6 are selected from HDPE films, and the gram weight is 40-80 g / m 2 .

[0010] In the above technical solution, preferably, the glass wool layer 5 is selected from a material with a gram weight of 800 to 1500 g / m 2 Man-made inorganic fibers.

[0011] In the above technical solution, preferably, the fabric layer 1 is selected from a knitted fabric or a hem non-woven fabric, and its gram weight is 180-250g / m 2.

[0012] In the above technical solution, preferably, the non-woven fabric layer 7 is selected from spunbonded non-woven fabric, and its gram weight is 40-60 g / m 2 .

[0013] In the above technical solution, preferably, the polyurethane foam layer 3 is a polyurethane composite layer with aerogel particles distributed inside.

[0014] In the above technical solution, preferably, the method for preparing the polyurethane foam layer 3 comprises the following steps:

[0015] (a) preparing component A: adding 20-60 parts of polyether polyol A, 20-50 parts of polyether polyol B, 0.5-11 parts of open-cell polyether polyol, 0.2-2.5 parts of foam stabilizer and 3-18 parts of water to container A in order by weight, stirring evenly and controlling the material temperature to be 19-22° C.; wherein the polyether polyol A is prepared by polymerization of ethylene oxide and propylene oxide with glycerol as the initiator, has a functionality of 3, a molecular weight of 4000-6000 and a hydroxyl value of 25-45 mgKOH / g; The polyether polyol B is prepared by polymerization of propylene oxide with glycerol and sorbitol as mixed initiators, with a functionality of 3 to 6 and a molecular weight of 300 to 600; the open-cell polyether polyol is prepared by polymerization of ethylene oxide and propylene oxide with glycerol as the main initiator, with a functionality of 3 to 5, a molecular weight of 7000 to 9000, a hydroxyl value of 25 to 40 mgKOH / g, and an EO content of 65 to 80%; the foam stabilizer comprises, by weight, 0.1 to 1.5 parts of foam stabilizer A and 0.1 to 2.1 parts of foam stabilizer B;

[0016] (b) preparing component B: adding isocyanate component into container B and stirring evenly;

[0017] (c) Preparation of component C: adding a small molecule compound to a reaction kettle, stirring and evacuating, controlling the temperature at 60-90° C., drying until the water content is ≤0.01wt%, and replacing with nitrogen, adding a catalyst dropwise, wherein the weight ratio of the small molecule compound to the catalyst is 0-10:0.1-2.0, wherein the catalyst is composed of a tertiary amine catalyst A and an organic metal catalyst B in a weight ratio of 0-0.8:0.1-2.0, and the weight ratio of component A to component C is 100:0.5-10, and stirring uniformly to obtain component C;

[0018] (d) mixing the intumescent flame retardant material and the porous nanomaterial in a weight ratio of 1:1 to 10 so that the porous nanomaterial is relatively evenly attached to the surface of the intumescent flame retardant material, and drying at a temperature of 60° C. for 2 hours to obtain component D;

[0019] (e) In terms of weight ratio, component A: component B: component C: component D = 100: 85-250: 0.5-10: 10-55, the ambient temperature is controlled at 19-22° C., component D is added to component B and mixed rapidly, then component A is added, stirred for 15-25 seconds, and then component C is added, the speed is increased, and stirred rapidly for 5-25 seconds. After stirring evenly, the mixture is immediately poured into a foaming box for foaming, and the foam is sliced ​​after ripening to obtain a polyurethane foam layer 3.

[0020] In the above technical solution, preferably, the weight ratio of the small molecule compound to the catalyst is 2-8:0.3-1.1.

[0021] In the above technical solution, preferably, the weight ratio of the catalyst in component A to component C is 100:0.1-2.0; the weight ratio of the small molecule compound in component A to component C is 100:0-10.

[0022] In the above technical solution, preferably, the weight ratio of the catalyst in component A to component C is 100:0.3-1.1; the weight ratio of the small molecule compound in component A to component C is 100:2-8.

[0023] In the above technical scheme, preferably, the small molecule compound in component C is selected from at least one of CHE-220, CHE-210, CHE-204, PEG-200, PEG-400, diethanolamine, ethylenediamine, ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, hexylene glycol, diethylene glycol or dipropylene glycol, and is dehydrated to have a water content of ≤0.01wt%.

[0024] In the above technical scheme, preferably, the tertiary amine catalyst A is selected from at least one of NE1070, NE1090, NE317, LED103 or LE15; the organic metal catalyst B is selected from at least one of T-9, T-12, bismuth isooctanoate, bismuth laurate, bismuth neodecanoate or bismuth cyclopentanoate.

[0025] In the above technical solution, preferably, the expanded flame retardant material in component D is selected from at least one of aluminum oxide, alum or expanded graphite.

[0026] In the above technical solution, preferably, the porous nanomaterial is selected from at least one of activated carbon, nano calcium hydroxide, nano calcium carbonate or white carbon black.

[0027] In the above technical solution, preferably, the expansion ratio of the expandable flame retardant material is greater than 200.

[0028] In the above technical solution, preferably, the weight ratio of the expanded flame retardant material to the porous nanomaterial is 1:2-8.

[0029] In the above technical solution, preferably, the weight ratio of component A to component D is 100:30-55.

[0030] In the above technical solution, preferably, the foam stabilizer A is selected from at least one of ECOADD S-2333, DC2525 or DC193; and the foam stabilizer B is selected from at least one of L6915, B8409, B8450 or B8228.

[0031] In the above technical solution, preferably, the isocyanate is selected from at least one of pure MDI, crude MDI, PM200, M20S, 5005, carbonized diamine-modified MDI, MDI-50 or TDI.

[0032] The sound-absorbing and noise-reducing lightweight new energy vehicle provided by the present invention has a structural improvement on the front hood. By using a combination of lightweight polyurethane foam and glass wool, the dual structural advantages of the internal porous structure of the lightweight polyurethane foam and the large number of tiny pores connected inside and outside of the glass wool are combined, so that noise enters the porous structure and is reflected multiple times, causing vibration and friction of air molecules in the gaps, converting sound energy into heat energy, greatly reducing energy, and achieving the effect of sound absorption and noise reduction; at the same time, the overall gram weight of the front hood is 2000g / m 2 Below, much lower than the front hatch of plastic parts (gram weight is usually 2500 ~ 3000g / m 2 In addition, combined with the arrangement of the fabric layer, the non-woven fabric layer and the adhesive layer, the overall front bonnet has high strength, good elongation, and is easy to form, and the fabric color can be customized, and the appearance is more beautiful; thereby making the overall weight of the new energy vehicle lighter, which is beneficial to extending the cruising range of the vehicle, and at the same time has the advantages of sound absorption and noise reduction, and the front bonnet has a more beautiful appearance. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Attached Figure 1 It is a structural schematic diagram of a front hatch hood 9 of a new energy vehicle that is sound-absorbing, noise-reducing and lightweight.

[0034] Attached Figure 1 In the figure, 1 is a fabric layer, 2 is a first bonding layer, 3 is a polyurethane foam layer, 4 is a second bonding layer, 5 is a glass wool layer, 6 is a third bonding layer, and 7 is a non-woven fabric layer.

[0035] Attached Figure 2 It is a simplified structural diagram of a new energy vehicle that absorbs sound, reduces noise and is lightweight.

[0036] Attached Figure 2In the figure, 8 is an engine hood, 9 is a front hatch, 10 is a cavity for accommodating cables, 11 is a front of the vehicle, and 12 is a vehicle body. DETAILED DESCRIPTION

[0037] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0038] Table 1 List of raw materials

[0039]

[0040]

[0041] [Example 1]

[0042] A new energy vehicle with sound absorption and noise reduction, lightweight, comprises a body 12 and a front 11, the front 11 comprises an engine cover 8, a front hatch 9 and a cavity 10 for accommodating cables, the front hatch 9 comprises a fabric layer 1, a first bonding layer 2, a polyurethane foam layer 3, a second bonding layer 4, a glass wool layer 5, a third bonding layer 6 and a non-woven fabric layer 7 from top to bottom; wherein the fabric layer 1 has a gram weight of 180 g / m 2 The first adhesive layer 2, the second adhesive layer 4 and the third adhesive layer 6 are 50g / m 2 HDPE film; the density of the polyurethane foam layer 3 is 12kg / m 3 , thickness is 15mm; glass wool layer 5 has a gram weight of 850g / m 2 The nonwoven fabric layer 7 has a gram weight of 50 g / m 2 Spunbond nonwoven fabric.

[0043] The preparation of the front hatch 9 includes the following steps:

[0044] a. Stack the material layers from top to bottom in order: fabric layer 1, first adhesive layer 2, polyurethane foam layer 3, second adhesive layer 4, glass wool layer 5, third adhesive layer 6 and non-woven fabric layer 7;

[0045] b. The seven layers of material in step a are heated simultaneously and then compression molded to obtain a front hatch.

[0046] The performance test data of the prepared front hood are shown in Table 2. The NVH performance test of the new energy vehicle and the result data of the cab noise test are shown in Table 3.

[0047] [Example 2]

[0048] A new energy vehicle with sound absorption and noise reduction and light weight includes a body 12 and a front 11. The front 11 includes an engine cover 8, a front hatch 9 and a cavity 10 for accommodating cables. The front hatch 9 includes a fabric layer 1, a first bonding layer 2, a polyurethane foam layer 3, a second bonding layer 4, a glass wool layer 5, a third bonding layer 6 and a non-woven fabric layer 7 from top to bottom. The fabric layer 1 has a gram weight of 200 g / m 2 The first adhesive layer 2, the second adhesive layer 4 and the third adhesive layer 6 are 50g / m 2 HDPE film; the density of the polyurethane foam layer 3 is 15kg / m 3 , thickness is 20mm; glass wool layer 5 has a gram weight of 1000g / m 2 The nonwoven fabric layer 7 has a gram weight of 50 g / m 2 Spunbond nonwoven fabric.

[0049] The preparation of the front hatch 9 includes the following steps:

[0050] (a) Preparation of component A: Add 59 parts of HEP-330N, 20 parts of NJ-4110, 0.5 parts of SK-350D, 1.5 parts of DC2525, 1.0 parts of B 8228, and 18 parts of water to container A in order by weight, stir evenly and control the material temperature to 19-22°C;

[0051] (b) Preparation of component B: Add 100 parts of PM200 and 150 parts of MDI50 into container B and stir evenly;

[0052] (c) Preparation of component C: 5 parts of CHE-204 were added to a reaction kettle, stirred and evacuated, the temperature was controlled at 80° C., dried until the water content was ≤0.01 wt %, and replaced with nitrogen 3 times, 1.5 parts of bismuth neodecanoate and 0.5 parts of bismuth cyclohexaneate were added dropwise, and stirred to obtain component C;

[0053] (d) 5 parts of graphite ADT-249 and 30 parts of nano-calcium hydroxide were mixed evenly, so that the nano-calcium hydroxide was relatively evenly attached to the surface of the graphite ADT-249, and dried at a temperature of 60° C. for 2 hours to obtain component D;

[0054] (e) In terms of weight ratio, component A: component B: component C: component D = 100: 250: 7: 35, the ambient temperature is controlled at 19-22° C., component D is added to component B and mixed rapidly, then component A is added, stirred for 20 seconds, and then component C is added, the speed is increased, and stirred rapidly for 20 seconds. After stirring evenly, the mixture is immediately poured into a foaming box for foaming, and the foam is sliced ​​after ripening to obtain a polyurethane foam layer 3;

[0055] (f) stacking the material layers from top to bottom in order: fabric layer 1, first adhesive layer 2, polyurethane foam layer 3, second adhesive layer 4, glass wool layer 5, third adhesive layer 6 and non-woven fabric layer 7;

[0056] (g) The seven layers of material in step f are heated simultaneously and then compression molded to obtain a front hatch.

[0057] The performance test data of the prepared front hood are shown in Table 2. The NVH performance test of the new energy vehicle and the result data of the cab noise test are shown in Table 3.

[0058] [Example 3]

[0059] A new energy vehicle with sound absorption and noise reduction, lightweight, comprises a body 12 and a front 11, the front 11 comprises an engine cover 8, a front hatch 9 and a cavity 10 for accommodating cables, the front hatch 9 comprises a fabric layer 1, a first bonding layer 2, a polyurethane foam layer 3, a second bonding layer 4, a glass wool layer 5, a third bonding layer 6 and a non-woven fabric layer 7 from top to bottom; wherein the fabric layer 1 has a gram weight of 250g / m 2 The first adhesive layer 2, the second adhesive layer 4 and the third adhesive layer 6 are 60g / m 2 HDPE film; the density of the polyurethane foam layer 3 is 18kg / m 3 , thickness is 15mm; glass wool layer 5 has a gram weight of 1200g / m 2 The nonwoven fabric layer 7 has a gram weight of 50 g / m 2 Spunbond nonwoven fabric.

[0060] The preparation of the front hatch 9 includes the following steps:

[0061] a. Stack the material layers from top to bottom in order: fabric layer 1, first adhesive layer 2, polyurethane foam layer 3, second adhesive layer 4, glass wool layer 5, third adhesive layer 6 and non-woven fabric layer 7;

[0062] b. The seven layers of material in step a are heated simultaneously and then compression molded to obtain a front hatch.

[0063] The performance test data of the prepared front hood are shown in Table 2. The NVH performance test of the new energy vehicle and the result data of the cab noise test are shown in Table 3.

[0064] [Example 4]

[0065] A new energy vehicle with sound absorption and noise reduction and light weight includes a body 12 and a front 11. The front 11 includes an engine cover 8, a front hatch 9 and a cavity 10 for accommodating cables. The front hatch 9 includes a fabric layer 1, a first bonding layer 2, a polyurethane foam layer 3, a second bonding layer 4, a glass wool layer 5, a third bonding layer 6 and a non-woven fabric layer 7 from top to bottom. The fabric layer 1 has a gram weight of 200 g / m 2 The first adhesive layer 2, the second adhesive layer 4 and the third adhesive layer 6 are 60g / m 2 HDPE film; the density of the polyurethane foam layer 3 is 18kg / m 3 , thickness is 20mm; glass wool layer 5 has a gram weight of 1100g / m 2 The nonwoven fabric layer 7 has a gram weight of 50 g / m 2 Spunbond nonwoven fabric.

[0066] The preparation of the front hatch 9 includes the following steps:

[0067] a. Stack the material layers from top to bottom in order: fabric layer 1, first adhesive layer 2, polyurethane foam layer 3, second adhesive layer 4, glass wool layer 5, third adhesive layer 6 and non-woven fabric layer 7;

[0068] b. The seven layers of material in step a are heated simultaneously and then compression molded to obtain a front hatch.

[0069] The performance test data of the prepared front hood are shown in Table 2. The NVH performance test of the new energy vehicle and the result data of the cab noise test are shown in Table 3.

[0070] [Example 5]

[0071] A new energy vehicle with sound absorption and noise reduction, lightweight, comprises a body 12 and a front 11, the front 11 comprises an engine cover 8, a front hatch 9 and a cavity 10 for accommodating cables, the front hatch 9 comprises a fabric layer 1, a first bonding layer 2, a polyurethane foam layer 3, a second bonding layer 4, a glass wool layer 5, a third bonding layer 6 and a non-woven fabric layer 7 from top to bottom; wherein the fabric layer 1 has a gram weight of 230 g / m 2 The first adhesive layer 2, the second adhesive layer 4 and the third adhesive layer 6 are 50g / m 2 HDPE film; the density of the polyurethane foam layer 3 is 15kg / m 3 , thickness is 15mm; glass wool layer 5 has a gram weight of 1000g / m 2 The nonwoven fabric layer 7 has a gram weight of 40 g / m 2 Spunbond nonwoven fabric.

[0072] The preparation of the front hatch 9 includes the following steps:

[0073] a. Stack the material layers from top to bottom in order: fabric layer 1, first adhesive layer 2, polyurethane foam layer 3, second adhesive layer 4, glass wool layer 5, third adhesive layer 6 and non-woven fabric layer 7;

[0074] b. The seven layers of material in step a are heated simultaneously and then compression molded to obtain a front hatch.

[0075] The performance test data of the prepared front hood are shown in Table 2. The NVH performance test of the new energy vehicle and the result data of the cab noise test are shown in Table 3.

[0076] [Comparative Example 1]

[0077] A commercially available new energy vehicle, the front hood of which is an injection-molded plastic part, and its gram weight data is shown in Table 2; the NVH performance test of the new energy vehicle is carried out using the same method as in Examples 1 to 5, and the result data of the cab noise test are shown in Table 3.

[0078] Table 2 Performance test data of automobile front hood in Examples 1 to 5 and Comparative Example 1

[0079]

[0080] Note: The performance tests of the plastic front hood of Comparative Example 1 and the composite sheet front hood of Examples 1 to 5 are different and not comparable. The “ / ” in Table 2 indicates that the corresponding performance has not been tested.

[0081] Table 3 Cabin noise detection data in NVH performance test of new energy vehicles in Examples 1 to 5 and Comparative Example 1

[0082]

[0083] Note: The noise detection in Table 3 adopts static testing, that is, when the car is static, the sound source is simulated by using a speaker, the noise data at the position of the driver's ear in the cab is detected, and the frequency and noise spectrum analysis is performed.

[0084] It can be seen from the data in Table 2 that the light-weight new energy vehicle with sound absorption and noise reduction provided by the present invention has a front hood with a weight of no more than 2000 g / m 2 The physical performance index requirements can still be met under the condition of , and can be used in the front hood of the automobile, and its gram weight is much lower than the plastic parts of Comparative Example 1, and the weight is lighter, which makes the overall weight of the new energy vehicle lighter; at the same time, it can be seen from the data in Table 3 that in the automobile NVH acoustic performance test, the noise of Examples 1 to 5 is lower, especially the noise in the medium and high frequency bands of 2000 to 8000 Hz is much lower than the plastic parts of Comparative Example 1, and the effect of sound absorption and noise reduction is significant; in addition, the front hoods of Examples 1 to 5 can be customized in fabric color according to customer requirements, which is easy to shape and the product is more beautiful.

[0085] It can be seen that the new energy vehicle of the present invention has the advantages of light weight, sound absorption and noise reduction, and beautiful front hood appearance, and can be used in the industrial production of new energy vehicles.

Claims

1. A new energy vehicle with sound absorption and noise reduction and light weight, comprising a vehicle body (12) and a front vehicle head (11), wherein the front vehicle head (11) comprises an engine cover (8), a front hatch (9) and a cavity (10) for accommodating cables, characterized in that: The front hatch cover (9) comprises, from top to bottom, a fabric layer (1), a first adhesive layer (2), a polyurethane foam layer (3), a second adhesive layer (4), a glass wool layer (5), a third adhesive layer (6) and a non-woven fabric layer (7); and the preparation method of the front hatch cover (9) comprises the following steps: a. stacking the material layers from top to bottom in order: the fabric layer (1), the first adhesive layer (2), the polyurethane foam layer (3), the second adhesive layer (4), the glass wool layer (5), the third adhesive layer (6) and the non-woven fabric layer (7); b. After heating the seven layers of materials in step a simultaneously, compression molding is performed to obtain a front hatch.

2. The sound-absorbing, noise-reducing, lightweight new energy vehicle according to claim 1, characterized in that: The density of the polyurethane foam layer (3) is 10-18 kg / m 3 , thickness is 15~25mm.

3. The sound-absorbing, noise-reducing, lightweight new energy vehicle according to claim 1, characterized in that: The first adhesive layer (2), the second adhesive layer (4) and the third adhesive layer (6) are selected from HDPE films, and the gram weight is 40-80 g / m 2 .

4. The sound-absorbing, noise-reducing, lightweight new energy vehicle according to claim 1, characterized in that: The glass wool layer (5) is selected from a material having a gram weight of 800 to 1500 g / m 2 Man-made inorganic fibers.

5. The sound-absorbing, noise-reducing, lightweight new energy vehicle according to claim 1, characterized in that: The fabric layer (1) is selected from a knitted fabric or a hemmed nonwoven fabric, and has a gram weight of 180-250 g / m 2 The non-woven fabric layer (7) is selected from spunbond non-woven fabric, and its gram weight is 40~60g / m 2 .

6. The sound-absorbing, noise-reducing, lightweight new energy vehicle according to claim 1, characterized in that: The polyurethane foam layer (3) is a polyurethane composite layer with aerogel particles distributed inside.

7. The sound-absorbing, noise-reducing, lightweight new energy vehicle according to claim 1, characterized in that: The method for preparing the polyurethane foam layer (3) comprises the following steps: (a) preparing component A: adding 20-60 parts of polyether polyol A, 20-50 parts of polyether polyol B, 0.5-11 parts of open-cell polyether polyol, 0.2-2.5 parts of foam stabilizer and 3-18 parts of water to container A in order by weight, stirring evenly and controlling the material temperature to be 19-22° C.; wherein the polyether polyol A is prepared by polymerization of ethylene oxide and propylene oxide with glycerol as the initiator, has a functionality of 3, a molecular weight of 4000-6000 and a hydroxyl value of 25-45 mgKOH / g; The polyether polyol B is prepared by polymerization of propylene oxide with glycerol and sorbitol as mixed initiators, with a functionality of 3 to 6 and a molecular weight of 300 to 600; the open-cell polyether polyol is prepared by polymerization of ethylene oxide and propylene oxide with glycerol as the main initiator, with a functionality of 3 to 5, a molecular weight of 7000 to 9000, a hydroxyl value of 25 to 40 mgKOH / g, and an EO content of 65 to 80%; the foam stabilizer comprises, by weight, 0.1 to 1.5 parts of foam stabilizer A and 0.1 to 2.1 parts of foam stabilizer B; (b) preparing component B: adding isocyanate component into container B and stirring evenly; (c) Preparation of component C: adding a small molecule compound to a reaction kettle, stirring and evacuating, controlling the temperature at 60-90° C., drying until the water content is ≤0.01wt%, and replacing with nitrogen, adding a catalyst dropwise, wherein the weight ratio of the small molecule compound to the catalyst is 0-10:0.1-2.0, wherein the catalyst is composed of a tertiary amine catalyst A and an organic metal catalyst B in a weight ratio of 0-0.8:0.1-2.0, and the weight ratio of component A to component C is 100:0.5-10, and stirring uniformly to obtain component C; (d) mixing the intumescent flame retardant material and the porous nanomaterial in a weight ratio of 1:1 to 10 so that the porous nanomaterial is relatively evenly attached to the surface of the intumescent flame retardant material, and drying at a temperature of 60° C. for 2 hours to obtain component D; (e) In terms of weight ratio, component A: component B: component C: component D = 100: 85-250: 0.5-10: 10-55, the ambient temperature is controlled at 19-22°C, component D is added to component B and mixed rapidly, then component A is added, stirred for 15-25 seconds, and then component C is added, the speed is increased, and stirred rapidly for 5-25 seconds. After stirring evenly, the mixture is immediately poured into a foaming box for foaming, and the foam is sliced ​​after ripening to obtain a polyurethane foam layer (3).

8. The sound-absorbing, noise-reducing, lightweight new energy vehicle according to claim 7, characterized in that: The small molecule compound is selected from at least one of CHE-220, CHE-210, CHE-204, PEG-200, PEG-400, diethanolamine, ethylenediamine, ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, hexylene glycol, diethylene glycol or dipropylene glycol, and is dehydrated to have a water content of ≤0.01wt%.

9. The sound-absorbing, noise-reducing, lightweight new energy vehicle according to claim 7, characterized in that: The tertiary amine catalyst A is selected from at least one of NE1070, NE1090, NE317, LED103 or LE15; the organic metal catalyst B is selected from at least one of T-9, T-12, bismuth isooctanoate, bismuth laurate, bismuth neodecanoate or bismuth cyclohexane; the foam stabilizer A is selected from at least one of ECOADDS-2333, DC2525 or DC193; the foam stabilizer B is selected from at least one of L6915, B8409, B8450 or B8228; the isocyanate is selected from at least one of pure MDI, crude MDI, PM200, M20S, 5005, carbonized diamine modified MDI, MDI-50 or TDI.

10. The sound-absorbing, noise-reducing, lightweight new energy vehicle according to claim 7, characterized in that: The expanded flame retardant material is selected from at least one of aluminum oxide, alum or expanded graphite; the porous nano material is selected from at least one of activated carbon, nano calcium hydroxide, nano calcium carbonate or white carbon black.